Distribution of nutrients and trace elements in forest soils of Singapore. (May 2019) - Leitgeb, Ernst; Ghosh, Subhadip; Dobbs, Marcus; Englisch, Michael; Michel, Kerstin
Abstract: Information on chemical fertility status and on trace element concentrations for Singapore soils is sparse. In this study, concentration and distribution of nutrients and trace elements in forest soils of Singapore, and the effect of geology on the current conditions of soils, were evaluated. Litter and mineral soil samples (0–10 cm, 10–20 cm, 20–50 cm) were divided into three groups according to geology (sedimentary rocks, Neogene-Quaternary sediments and igneous rocks). Basic soil properties, exchangeable cations including cation exchange capacity (CEC), and pseudototal concentrations of 17 elements including nutrients and potentially toxic elements (PTE; As, Cd, Cu, Cr, Ni, Pb, Zn) were determined. Results showed that the soils of Singapore were acidic (pH 3.7–6.2) and characterised by a low CEC (maximum mean value: 100 mmolc kg −1 ) and low P concentrations (mean values of 0.28 g kg −1 or less) irrespective of geology. Pseudototal concentrations of PTE were also low, except for As. However, significantly (p < 0.05) higher concentrations of soil organic carbon, total P, base forming elements, exchangeable base cations and PTE (except As and Cd) were found in soils developed on sedimentary rocks and Neogene-Quaternary sediments compared to those developed on igneous rocks. Although total N and S concentrations did not differ significantly between the three geological groups, the differences in nutrient status were more pronounced than in trace element levels across geology. The properties of forest soils, which are mainly unaffected by anthropogenic activities, vary depending on the parent material, i.e. igneous or sedimentary rocks and Neogene-Quaternary sediments. Highlights: A comprehensive data set for Singapore soils with reference to geology is presented. Geology is particularly important for soil nutrient status. Trace element concentrations in forest soils are generally low. Arsenic concentrations are elevated in soils developed on igneous rocks. These data can be used to assess soil pollution in Singapore.